1952
DOI: 10.1177/004051755202201105
|View full text |Cite
|
Sign up to set email alerts
|

Nonfreezing Water and Nonfreezing Benzene Capacities of Cottons and Modified Cottons

Abstract: W HEN cellulosic fibers containing moisture are cooled below 0°C, all of the water will not freeze, even at very low temperatures [23,32,33]. A quantitative study of this phenomenon presents a new approach to the study of the cellulose-moisture relationship, which is of fundamental importance in a wide variety of cotton textile problems since the physical properties of the fibers are very sensitive to changes in moisture content.Details of the application of the calorimetric, heatof-fusion method for determini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

1963
1963
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This represents a minimum void fraction of 30% and an internal area wliich is at least 19 m2/g cellulose and is probably considerably greater. Other evidence of substantial internal voids in dried native fibers is also available [ 12,14,20,33,48] although there is recent strong contrary evidence [44]. A moderately porous dry-fiber structure is consistent with the present results which indicate an accessible surface many times the superficial external area.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…This represents a minimum void fraction of 30% and an internal area wliich is at least 19 m2/g cellulose and is probably considerably greater. Other evidence of substantial internal voids in dried native fibers is also available [ 12,14,20,33,48] although there is recent strong contrary evidence [44]. A moderately porous dry-fiber structure is consistent with the present results which indicate an accessible surface many times the superficial external area.…”
Section: Resultssupporting
confidence: 89%
“…The desire for greater effectiveness of this type of molecule has led to the use of highly chlorinated hydrocarbons which are watersoluble by virtue of sulfonic [24,30] and sulfonamide [20,25 J groups and have an insectproofing effect by virtue of their chlorine content [13]. Certain anionic surface-active agents, which contain sulfonic acid groups and would be held by the wool in a manner similar to most dyes, also possess activity against larvae of the clothes moth ( T ineola bisselliella) and the carpet beetle (Anthrenus flavipes) (22], but poor washand.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 The presence of a strongly bound monolayer of water on cotton has been consistent historically with thermal calculations (90 cal/g) approximating that of the heat of fusion for ice, and validating the hydrogen bonding forces to cellulose. 38,[40][41][42][43] From this state further water sorption then assumes the character of capillary condensation and has been characterized as free water, i.e. perturbed and unperturbed water.…”
Section: Water Bindingmentioning
confidence: 99%
“…In 1947-52, Magne et al (11,12) measured amounts of freezing and nonfreezing water in moist cellulose at -4.5°C. They found that all water was nonfreezing up to about 0.04 g/g native cotton, that about half of the water between 0.04 and 0.15-0.20 g/g was nonfreezing, and that all of the water above 0.15-0.20 g/g was freezing.…”
Section: Bound Watermentioning
confidence: 99%